2018
DOI: 10.3329/jbau.v16i1.36478
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide based weed management in aromatic rice of Bangladesh

Abstract: Selection of appropriate weed management strategy helps reduce rice yield loss due to weeds. Despite some undesirable side-effects, no viable alternative is currently available to shift the chemical weed management in rice. However, time of herbicide application is very important with respect to its efficacy. Keeping in mind the inevitability of herbicidal weed control, the current study was designed to evaluate the response of selected aromatic fine rice varieties of Bangladesh to different herbicides based w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…The highest number of effective tillers hill -1 (17.562) was found in BRRI dhan65 where effective tillers hill -1 of BRRI dhan83 was 11.342. Significant variations in number of effective tillers hill -1 among the different varieties were also reported by Islam et al (2018). The highest panicle length (22.688 cm), number of grains panicle -1 (104.177), sterile grains panicle -1 (42.667), and 1000 grains weight (26.573 gm) were obtained from BRRI dhan83 and the lowest panicle length (21.308 cm), number of grains panicle -1 (83.497), sterile grains panicle -1 (33.317) and 1000 grains weight (23.610 gm) were obtained from BRRI dhan65.…”
Section: Effect Of Variety On Growth and Yield Attributes Of T Aus Ricementioning
confidence: 80%
“…The highest number of effective tillers hill -1 (17.562) was found in BRRI dhan65 where effective tillers hill -1 of BRRI dhan83 was 11.342. Significant variations in number of effective tillers hill -1 among the different varieties were also reported by Islam et al (2018). The highest panicle length (22.688 cm), number of grains panicle -1 (104.177), sterile grains panicle -1 (42.667), and 1000 grains weight (26.573 gm) were obtained from BRRI dhan83 and the lowest panicle length (21.308 cm), number of grains panicle -1 (83.497), sterile grains panicle -1 (33.317) and 1000 grains weight (23.610 gm) were obtained from BRRI dhan65.…”
Section: Effect Of Variety On Growth and Yield Attributes Of T Aus Ricementioning
confidence: 80%
“…Compared to the single application of pre-and post-emergence herbicide, the combination of them exerted 70% higher WCE than hand weeding of CT Table 5. The broad-spectrum activity and higher phytotoxic effects of herbicides [37]; [38] against both grass, broad-leaved, and even narrow-leaved weeds compared to a single application of each may explain the higher WCE in SP than CT. Retention of 50% rice straw residue produced lesser weed density and biomass than no-residue.…”
Section: Effect Of Treatments On Weed Density and Biomass Weed Contrmentioning
confidence: 99%
“…This result explains that the normal fertilization treatment it has an abundant amount of the two basic N and P elements to increase the plant height, while the crop plants remain lower when the fertilizer is not added due to the lack of the necessary mineral elements necessary for growth in the soil of the experiment except with a small amount that does not enable it to grow at its full potential. These results did not in agreement with Osman et al (20) and Kheyri et al (18) who indicated that organic and mineral foliar fertilizers lead to a significant increase in plant height compared to the normal fertilization treatment, nor are they consistent with Aljutheri et al (4) who They indicated that there were no significant differences between mineral and organic foliar fertilizers compared to normal fertilization.…”
Section: Plant Heightmentioning
confidence: 58%